Utilization of amino acids and dipeptides by Lactobacillus plantarum from orange in nutritionally stressed conditions - Saguir de Zucal, Fabiana Maria (2008)
To investigate amino acid and dipeptide utilization by Lactobacillus plantarum N4 isolated from orange peel, in a nutritionally depleted medium basedon MRS (Mann, Rogosa, Sharpe).Methods and Results: In MRS with 0 Æ1 g l)1 of meat extract and without peptone and yeast extract, growth increased when essential and stimulatory amino acids and nonessential amino acid were added to the medium. Replacement of the essential amino acid, leucine, and the nonessential amino acid, glycine, byleucyl-leucine (Leu-Leu) and ⁄or glycyl-glycine (Gly-Gly) significantly enhancedgrowth. Essential amino acids were mainly consumed and the dipeptides were almost completely used at the end of growth. Leucine and glycine accumulatedinternally from the peptides were higher than from the free amino acids.Glucose utilization increased in the media containing dipeptides comparedwith the medium containing free amino acids.Conclusions: In a N-depleted medium, Leu-Leu and ⁄or Gly-Gly were more effective than the respective amino acids in supporting growth of the microorganism. The more efficient internal accumulation of glycine and especially leucine from dipeptides confirmed the ability of the strain to assimilate mainly complex nitrogen molecules rather than simple ones.Significance and Impact of the Study: The ability of Lact. plantarum N4 to efficiently use dipeptides could contribute to spoilage development in the natural medium of the organism, orange juice